PENGARUH JIWA KEWIRAUSAHAAN DAN KEMANDIRIAN PRIBADI TERHADAP KEBERHASILAN USAHA CATERING IBU RIA DI KOTA MEDAN - ELISHA SUNIJATI; DEVINAWATY . (LP2MTBM MAKARIOZ, 2020)
One of the catering businesses in Medan City is Mrs. Ria's catering business, where Mrs. Ria's catering has not been able to compete with catering throughout Medan City, because of the limited number of consumers, so the business is not so developed, where the consumers are still not as many as other caterers. where there was a decline in consumers during the period of 2017-2020, which was caused by mrs. Ria's entrepreneurial spirit which still did not appear when opening this catering business, so that there are still many foods that cannot be created properly, so that the menu served by the menu is just that and not varied, thus making the ability to develop this business is still far away. This study aims to find out how the influence of Mrs. Ria's entrepreneurial spirit and personal independence attitude on the sustainability of Mrs. Ria's Catering business. The total population in this study amounted to 60 businessmen in the east field, where the sample-taking technique used a saturated sample technique with a sample of 60 businessmen. The results of the study can be concluded that simultaneously the variables of mrs. Ria's entrepreneurial spirit and personal self-esteem have a significant effect on the success of Mrs. Ria's catering business. Meanwhile, partially, only the variable of Mrs. Ria's entrepreneurial spirit is dependent on the variable of the success of Mrs. Ria's catering business.